St. Ives; being the adventures of a French prisoner in England - Stevenson, Robert Louis, 1850-1894; Colvin, Sidney, 1845-1927; Quiller-Couch, Arthur, 1863-1944 (New York : C. Scribner's sons, 1912)
From the creator of Treasure Island and Kidnapped, and written while he lived in Samoa, this was the author's last title. Stevenson had written all but the very conclusion of this work at the time of his death. His stepdaughter had been serving as his secretary and was in possession of an outline for the ending. In order to conclude the story the publisher enlisted the talents of Sir Arthur Quiller-Couch who supplied the last few chapters. The book plot concerns the adventures of the dashing Viscomte Anne de Keroual de St. Ives, a Napoleonic soldier enlisted as a private under the name Champdivers, after his capture by the British.
"... The ... task of supplying the missing chapters has been intrusted to Mr. Quiller-Couch, whose work begins at chapter XXXI."-- Editorial note.
Editorial note signed : S. C.
Mode of access: Internet.
Keywords: 1800-1899; Napoleonic Wars, 1800-1815 -- Prisoners and prisons -- Fiction; Fiction